Modeling Chandy–Lamport Distributed Snapshot Algorithm Using Colored Petri Net - Pashazadeh, Saeid; Al-Basseer, Basheer Zuhair Jaafar; Tanha, Jafar (IET software, 2024)
Distributed global snapshot (DGS) is one of the fundamental protocols in distributed systems. It is used for different applications like collecting information from a distributed system and taking checkpoints for process rollback. The Chandy–Lamport protocol (CLP) is famous and well‐known for taking DGS. The main aim of this protocol was to generate consistent cuts without interrupting the regular operation of the distributed system. CLP was the origin of many future protocols and inspired them. The first aim of this paper is to propose a novel formal hierarchical parametric colored Petri net model of CLP. The number of constituting processes of the model is parametric. The second aim is to automatically generate a novel message sequence chart (MSC) to show detailed steps for each simulation run of the snapshot protocol. The third aim is model checking of the proposed formal model to verify the correctness of CLP and our proposed colored Petri net model. Having vital tools helps greatly to test the correct operation of the newly proposed distributed snapshot protocol. The proposed model of CLP can easily be used for visually testing the correct operation of the new future under‐development DGS protocol. It also permits formal verification of the correct operation of the new proposed protocol. This model can be used as a simple, powerful, and visual tool for the step‐by‐step run of the CLP, model checking, and teaching it to postgraduate students. The same approach applies to similar complicated distributed protocols.